The Role Of Governance And Transfer Pricing In Affecting Tax Avoidance: A Study Of Technology Companies - Wibisono, Medeliene; Permatasari, Intan Kurnia (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of corporate governance and transfer pricing on tax avoidance in technology companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2022. The independent variables used in this study are audit committee, independent commissioner, institutional ownership, managerial ownership, and transfer pricing, while the dependent variable is tax avoidance which is proxied by the effective tax rate (ETR). This study uses a quantitative approach with multiple linear regression analysis methods. The results of the study indicate that the audit committee and transfer pricing have a significant effect on tax avoidance, while independent commissioners, institutional ownership, and managerial ownership do not have a significant effect.